2018
DOI: 10.21608/agro.2018.2944.1095
|View full text |Cite
|
Sign up to set email alerts
|

Seed pre-soaking on Gibberellic acid (GA3) enhance growth, histological and physiological traits of sugar beet (Beta vulgaris L.) under water stress Enas, S. Ibrahim Botany Department, Faculty of Agriculture, Suez Canal University, 41522 Ismailia, Egypt

Abstract: T HE PRESENT study aimed to evaluate the effect of three levels of gibberellic acid solutions (50, 100 and 150 mg/L) on two sugar beet cultivars. (Farida and Sultan) under three field capacity (50 , 75 and 100%). This experiment was carried out at the Experimental Farm, Faculty of Agriculture, Suez Canal University, Ismailia, during the two growing successive seasons of 2013/14 and 2014/15. Results showed that all GA3 tested treatments statistically improved growth parameters, i.e., number of leaves, fresh and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The underlying mechanism behind the higher seed yield produced by growth regulators has been attributed to improved biosynthesis in the assimilates which are directly related to yield, as GA foliar application on 30-day-old seedlings produced higher yields in mustard, while GA (100 ppm) also produced the highest soybean seed yield [109]. Similar to our findings, it was reported that GA triggered vegetative growth in crop plants by increasing plant height, stem diameter, weight and leaf numbers, and the plants' fresh and dry weights [110][111][112][113], which led to higher biomass productivity. Seed and biological yield are vital indicators for determining the effectiveness of foliar-applied phytohormones.…”
Section: Discussionsupporting
confidence: 86%
“…The underlying mechanism behind the higher seed yield produced by growth regulators has been attributed to improved biosynthesis in the assimilates which are directly related to yield, as GA foliar application on 30-day-old seedlings produced higher yields in mustard, while GA (100 ppm) also produced the highest soybean seed yield [109]. Similar to our findings, it was reported that GA triggered vegetative growth in crop plants by increasing plant height, stem diameter, weight and leaf numbers, and the plants' fresh and dry weights [110][111][112][113], which led to higher biomass productivity. Seed and biological yield are vital indicators for determining the effectiveness of foliar-applied phytohormones.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, the sucrose % increased by increasing gibberellic concentration up to 300 ppm in the first growing season and up to 200 ppm in the second growing season. Similar findings were mentioned by Azab et al (2018) and El-Kady and El-Mansoub (2020). On the contrary, Leilah and Khan (2021) found that sucrose % decreased with increasing gibberellic acid levels.…”
Section: Sucrose %supporting
confidence: 89%
“…and caused an appreciable increase in root and top dry weight/plant as well as the lowest quantities of sugar lost to molasses in both growing seasons. Azab et al (2018) tested the effect of three levels of gibberellic acid solutions (50, 100 and 150 mg/L) on two sugar beet cultivars (Farida and Sultan), and results showed that all tested GA3 treatments statistically improved root yield, sucrose% of sugar beet. El-Kady and El-Mansoub (2020) studied the effect of (gibberellic acid GA3), at the levels of 0, 100, 200 and 300 ppm concentrations on growth, yield and quality of sugar beet.…”
Section: Ekbmentioning
confidence: 99%
“…Nonetheless, the maximum biomass yield (1.98 g plant −1 ) was obtained after twice applying GA 3 @ 300 ppm, while the minimum biomass yield (0.98 g plant −1 ) was obtained for the control treatment. It was reported in many studies that GA 3 enhanced the plant growth by increasing fresh and dry weights of leaves, number of leaves per plant (Azab, 2018;Iftikhar et al, 2020), plant height, biomass, stem weight, stem diameter, and the number of stems (Ullah et al, 2017). Previously, a significant effect of GA 3 on the biological yield, stover yield and harvest index was observed in mungbean (Beall et al, 1996;Uddin, 1999;Alam et al, 2018;Rahman et al, 2018).…”
Section: Biomass Yieldmentioning
confidence: 99%